A Typology of the Perceived External Barriers Hindering Export of Agricultural Products in Iran - Yeganeh, Hamid; Saeid, Masoome (Journal of Comparative International Management, 2011)
This study attempts to explore, understand, and classify the external barriers to the export of agricultural products as perceived by the small businesses operating in Iran. The data are collected from twenty external export barriers, including the Trade Embargo/Political Friction, Inflation, Slow Collection of Payments from Abroad, and Currency Exchange Rate for evaluation. These areas are considered highly important for the purpose of this analysis. Our analysis recognized seven thematically classified export barriers. Those barriers were further analyzed and the following categories are found significant: Unfavorable Domestic Conditions, Governmental Barriers, and Procedural Barriers. In view of the Iranian socio-economic environment, the underlying factors are discussed and implications are pointed out.